2002
DOI: 10.1007/s11743-002-0240-y
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly of compounds based on a glycerin skeleton as C‐3 building block. Part II

Abstract: Part I reviewed the properties of alkyl glyceryl ethers and their derivatives in forming self-assemblies such as liquid crystals. Part II covers strategies for the synthesis of several types of artificial ether lipids with a glycerin backbone, such as dicephalic surfactants, gemini surfactants, calamitic bolaamphiphiles, dendrimers, and membrane components of archaebacteria, which have been reported to constitute unique self-assemblies useful as materials for future nanochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It is concluded that the anisometric molecules with several types of segments bearing different properties as building blocks are suitable for designing unique ordered liquid crystals with characteristic mesophase morphologies compared to the conventional surfactants or lipids. These results demonstrate that this approach to control the supramolecular structure induced by ordered liquid crystals allows a novel highly ordered nano-structure bearing potential for many applications, such as display switches, light modulators, templates catalysts, drug delivery, artificial skin & muscle, photonics optical networks, gene therapy, electric sensors, to be manufactured [43,47,48]. In connection to these applications, novel liquid-crystalline with layer-like self-assembly, such as multi-lamellar liquid crystals by compound [B] or the bola-amphiphilic compounds [F] with shorter core and reducing the number of available hydrogen bonds together with the lateral alkyl chain replaced by semi-perfluorinated chain have been reported to show color changes [13,22].…”
Section: Liquid Crystals the Fourth State Of Matters And Their Futurmentioning
confidence: 81%
“…It is concluded that the anisometric molecules with several types of segments bearing different properties as building blocks are suitable for designing unique ordered liquid crystals with characteristic mesophase morphologies compared to the conventional surfactants or lipids. These results demonstrate that this approach to control the supramolecular structure induced by ordered liquid crystals allows a novel highly ordered nano-structure bearing potential for many applications, such as display switches, light modulators, templates catalysts, drug delivery, artificial skin & muscle, photonics optical networks, gene therapy, electric sensors, to be manufactured [43,47,48]. In connection to these applications, novel liquid-crystalline with layer-like self-assembly, such as multi-lamellar liquid crystals by compound [B] or the bola-amphiphilic compounds [F] with shorter core and reducing the number of available hydrogen bonds together with the lateral alkyl chain replaced by semi-perfluorinated chain have been reported to show color changes [13,22].…”
Section: Liquid Crystals the Fourth State Of Matters And Their Futurmentioning
confidence: 81%
“…Their use in newer synthetic approaches has been reviewed [43][44][45]. The presence of two free OH groups allows the introduction of much functionality for specific synthetic surfactants and specialty lipids.…”
Section: Etherification Of Glycerol Via Catalytic Dehydration 229mentioning
confidence: 99%
“…It is becoming more important for biodiesel producers to increase revenues by selling by-product of glycerol as well as finding use for other by-products. Purified glycerol has found many applications such as a substrate for chemical synthesis (Alavi Nijke, 2007;Aresta et al, 2009;Kim et al, 2007 Wolfson andDlugy, 2007), bioconversion (Chen et al, 2002;Kim et al, 2007;Nicol et al, 2012), substrate for food and cosmetic industry, production of surfactants (Jurado et al, 2012;Urata and Takaishi, 2002;Xu et al, 2011), production of biodegradable packaging (Liu et al, 2001), application in freezing (Izawa et al, 2004) or as a medium in medical care Nho et al, 2009). Other by-products such as crude glycerine or MONG fraction are not frequently reported in literature, their basic physicochemical properties are not described, there is no data on their possible application.…”
Section: Introductionmentioning
confidence: 99%